What Matters More in Explaining Drug Court Graduation and Rearrest: Program Features, Individual Characteristics, or Some Combination - Breno, Alex (International journal of offender therapy and comparative criminology, 2023)
This study examines the program- and individual-level factors that impact the success of drug court clients in terms of: (1) graduation; and (2) not being arrested while participating in the court program. The data consist of 848 individuals in nine drug courts. This paper discusses how different individual- and program-level factors impact the success of drug court participants. The findings suggest that individual- and program-level factors are both important in predicting program graduation and arrest during drug court participation, while controlling for participant demographics. Clients’ education, drug/alcohol usage, program staffing, and clinical standards impact program graduation while criminal history, drug/alcohol usage, number of program hours offered, program staffing, and use of rewards and sanctions predict in-program arrest. Models combining both program- and individual-level factors performed better than either alone, leading to recommendations that agencies should emphasize improving program quality while targeting clients’ needs to achieve greater success.